Physico-morphological variation in hyacinth bean [Lablab purpureus (L.) Sweet] - Islam, MS; Rahman, MM; Hossain, T (Bangladesh Journal of Agricultural Research, 2010)
Forty-four hyacinth bean genotypes were evaluated for different qualitative and quantitative characters during July 2005 to February 2006 at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur. The genotypes showed considerable variations for most of the morpho-physical traits. Shape, size and colour of vein, leaf, petiole, stem, flower, pod and seed varied among the genotypes. Days to first flower ranged from 47.6 to 136.3 days indicating the presence of early variety. Individual pod weight varied from 1.47 (HB042) to 12.3g (HB009). The genotype HB027 produced the maximum number of pods/ plant (425) closely followed by HB001 (385). Similar trend was observed for pod yield/plant. The genotype HB027 produced the highest pod yield/plant (3.45kg) followed by HB001 (3.35kg). 100-green seed weight ranged from 4.0g to 73.33g, which indicated the presence of bold seeded genotypes. Among the genotypes, HB027 and HB007 produced very bold green seed and higher green pod yield/plant, therefore, they can be selected for both pod and green seed production purpose. Keywords: Physico-morphological; hyacinth bean DOI: 10.3329/bjar.v35i3.6450 Bangladesh J. Agril. Res. 35(3) : 431-438